2021
DOI: 10.1038/s41598-021-95121-4
|View full text |Cite
|
Sign up to set email alerts
|

State dependent effects on the frequency response of prestin’s real and imaginary components of nonlinear capacitance

Abstract: The outer hair cell (OHC) membrane harbors a voltage-dependent protein, prestin (SLC26a5), in high density, whose charge movement is evidenced as a nonlinear capacitance (NLC). NLC is bell-shaped, with its peak occurring at a voltage, Vh, where sensor charge is equally distributed across the plasma membrane. Thus, Vh provides information on the conformational state of prestin. Vh is sensitive to membrane tension, shifting to positive voltage as tension increases and is the basis for considering prestin piezoel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Thus, we might expect that direct voltage-driven conformational changes in prestin could differ from unphysiological (e.g., salicylate or SO 4 2− ) anion-induced steady state cryo-EM structures. Interestingly, we have recently shown that the ΔC sa component of membrane capacitance exists only in the real (capacitive) part of complex NLC, not in the imaginary (conductive) part, ostensibly linking it directly to membrane bilayer influence rather than prestin charge movement 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we might expect that direct voltage-driven conformational changes in prestin could differ from unphysiological (e.g., salicylate or SO 4 2− ) anion-induced steady state cryo-EM structures. Interestingly, we have recently shown that the ΔC sa component of membrane capacitance exists only in the real (capacitive) part of complex NLC, not in the imaginary (conductive) part, ostensibly linking it directly to membrane bilayer influence rather than prestin charge movement 56 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the speed of the prestin-motor function in membrane patches, frequency-dependent electrical power consumption was determined directly from macro-patch NLC data reported and by Santos-Sacchi et al [21], replotted in Fig. 1 as the real Re ( C N ) (A) and imaginary Im ( C N ) (B) components.…”
Section: Resultsmentioning
confidence: 99%
“…2A, B and C show theoretical predictions for Re ( C N ), Im ( C N ) and P P respectively. For parameters approximated from the Santos-Sacchi et al data [21], PZT theory predicts band-pass power consumption to peak near 37 kHz. Results support the hypothesis that electrical power consumed by the prestin motor complex is band-pass and operates at frequencies much higher than would be implied by the low pass character of | C W |.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations